2018
DOI: 10.3847/1538-3881/aad085
|View full text |Cite
|
Sign up to set email alerts
|

The Warm Neptunes around HD 106315 Have Low Stellar Obliquities

Abstract: We present the obliquity of the warm Neptune HD 106315c measured via a series of spectroscopic transit observations. HD 106315c is a 4.4 R Earth warm Neptune orbiting a moderately rotating late F-star with a period of 21.05 days. HD 106315 also hosts a 2.5 R Earth super-Earth on a 9.55 day orbit. Our Doppler tomographic analyses of four transits observed by the Magellan/MIKE, HARPS, and TRES facilities find HD 106315c to be in a low stellar obliquity orbit, consistent with being well aligned with the spin axis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 73 publications
7
41
1
Order By: Relevance
“…Similar to GJ 9827, we aim to understand the stellar activity component of the radial velocity data through investigating the possible relationships between the K2 light curve, the Calcium II H&K and H-alpha stellar lines, and our radial velocity data. The projected rotational velocity measurement (v sin i = 13.2 ± 1 km s −1 ) combined with the obliquity measurement (λ = −10.9 ± 3.7, Zhou et al 2018) suggests a stellar rotation period of 4.78±0.15 days. HD 106315 was observed in K2 Campaign 10; this campaign had a 14 day data gap resulting in 49 days of contiguous data.…”
Section: Hd 106315 Stellar Activitymentioning
confidence: 85%
See 1 more Smart Citation
“…Similar to GJ 9827, we aim to understand the stellar activity component of the radial velocity data through investigating the possible relationships between the K2 light curve, the Calcium II H&K and H-alpha stellar lines, and our radial velocity data. The projected rotational velocity measurement (v sin i = 13.2 ± 1 km s −1 ) combined with the obliquity measurement (λ = −10.9 ± 3.7, Zhou et al 2018) suggests a stellar rotation period of 4.78±0.15 days. HD 106315 was observed in K2 Campaign 10; this campaign had a 14 day data gap resulting in 49 days of contiguous data.…”
Section: Hd 106315 Stellar Activitymentioning
confidence: 85%
“…Later Zhou et al (2018) investigated the system architecture through measuring the obliquity of HD 106315 c using Doppler tomography and constraining the mutual inclination of HD 106315 b through dynamical arguments. They found that these two planets both have low obliquities, consistent with the few other warm Neptunes with measured obliquities (eg.…”
Section: Hd 106315mentioning
confidence: 99%
“…We also made use of the CHIRON observations to measure the projected rotational velocity v sin I of the host stars. Following Zhou et al (2018), we model the line profiles derived from the CHIRON spectra via a convolution of kernels representing the rotation, radialtangential macroturbulence, and instrument broadening terms. The rotational and radial-tangential macroturbulence kernels follow the prescription in Gray (2005), while the instrument broadening kernel is represented by a Gaussian function of width that of the instrument resolution.…”
Section: Smarts 15 M / Chironmentioning
confidence: 99%
“…s 1 to account for the instrument broadening. The disk integration process is computationally intensive, as such we only compute a grid of broadening kernels spanning  grid during our model fit(Zhou et al 2018). By modeling the line profiles, we derive a projected stellar rotation rate of …”
mentioning
confidence: 99%